EFL Learners' Perception of Text Difficulty: What Lies Beyond Traditional Text Readability Formulas? - Fatemeh Rezaei (Journal of Education and Teacher Training Innovation, 2024)
The present study, adopting a mixed methods design, is in line with these recent studies which examines the relationship between text difficulty level and reading comprehension of a group of 112 pre-intermediate EFL learners. Moreover, in addition to two reading tests with less and more difficult passages, a semi-structured interview with 11 volunteer learners were devised to probe the perceptions of the learners about the elements contributing to text difficulty in reading comprehension tests. The results of the quantitative analysis indicated that there was a significant direct strong correlation between the test scores of the two reading tests with less and more difficult passages. In addition, the difference between the observed means of the two tests was significant. This implied that although the learners approached both tests in a similar manner, text difficulty could play a significant role in their achievement in reading test. The results of qualitative analysis also indicated that the role of background knowledge and vocabulary knowledge of the learners, as perceived by the participants of the study, have to be taken into account. Moreover, the text features such as the existence of cohesive devices and other inferential cues are of significance. The results confirm the significance of readability formula as a considerable means of measuring reading difficulty for EFL learners, and introduces the key roles of learners’ background knowledge and vocabulary knowledge as sources of perceived difficulty among learners. This is specifically important when determining the texts for different learners various ages and educational levels. An important implication of this study is that teaching and reading assessment need to consider factors such as students' vocabulary knowledge, knowledge background, coherence of the text, as well as the interaction between reader characteristics and text features. It is recommended that English as a foreign language (EFL) educators develop a more holistic approach to selecting and using reading texts taking into account not only traditional readability formulas, but also other important factors such as students' vocabulary knowledge, knowledge background, and level of text coherence.